Pulmonary Mucormycosis: An Emerging Infection. (12th December 2012) - Muqeetadnan, Mohammed; Rahman, Ambreen; Amer, Syed; Nusrat, Salman; Hassan, Syed; Hashmi, Syed
Abstract : Mucormycosis is a rare, but emerging, life-threatening, rapidly progressive, angioinvasive fungal infection that usually occurs in immunocompromised patients. We present a case of pulmonary mucormycosis in a diabetic patient who was on chronic steroid therapy for ulcerative colitis. Early recognition of this diagnosis, along with aggressive management, is critical to effective therapy and patient survival. The delay in diagnosis of this rapidly progressive infection can result in mortality.